Impact of ambiguity resolution on phase center offsets and hardware delay estimation for BDS-3 inter-satellite links - Li, Zongnan; Xiao, Wei; Fan, Lei; Lu, Zukun; Wang, Feixue (Frontiers in Physics, 2023)
The Chinese BeiDou navigation satellite system (BDS) has already completed its three phases and developed to a global navigation satellite system for open positioning, navigation, and time (PNT) service. The BDS-3 satellites feature the inter-satellite link (ISL). The ISL observation related errors model and ambiguity resolution for L-band observation are the crucial factors in precise data processing. In this study, we present the impact of ambiguity resolution on phase center offsets (PCOs) and hardware delay estimation of BDS-3 inter-satellite links for the first time. Two weeks of L-band observations from 99 globally distributed ground stations and Ka-band ISL observations are collected for experiment validation and analysis. Firstly, network solutions with and without ISL observations are conducted to investigate the role of ISL observation to ambiguity resolution. Afterwards, ISL observation related errors, mainly PCOs and hardware delay, are estimated by processing together L-band with ISL observations with and without ambiguity resolution to analyze the impact of ambiguity resolution on these two factors. Finally, orbit accuracy in the network solution is assessed to further validate the effectiveness of estimated PCOs and hardware delay in our experiment. The result indicates that introducing ISL can slightly improve the fixing rate compared to only L-band observations from 83.7% to 84.3%. Furthermore, ambiguity resolution plays a positive influence on the stability of estimated PCOs and hardware delay in turn, although the root mean square (RMS) values basically remain unchanged. The standard deviation (STD) of x-offset is reduced from 0.021 m to 0.012 m with great improvement of about 43%, while 0.022 m to 0.016 m with improvement of about 27% for y-offset. There is slightly improvement about 8% for z-offset. Similarly, around 10% improvement of STD for hardware delay can be achieved while the RMS values almost stay the same expect for C40. Orbit determination from network solutions shows high accuracy compared to the public products for the satellite with good geometry configuration, which further validate our estimates for ISL PCOs and hardware delay.